Faktor-Faktor Yang Memengaruhi Sustainable Entrepreneurship Pada Usaha Kecil Menengah Di Jakarta - Michael Kianto (Universitas Tarumanagara, 2019)
Entrepreneurship has both positive and negative contributions to our society. On the negative side, the degradation of environmental quality caused by entrepreneurial activities requires serious attention. As such, sustainable entrepreneurship has been suggested as an attempt to alleviate environmental problems. Furthermore, there are scant studies in regard to motivation and propensity in the development of sustainable entrepreneurs among SMEs practitioners. Thus, this study was conducted to address the factors associated with propensity for sustainable entrepreneurship among owners-managers of SMEs. This sample collection through purposive sampling. There are 100 respondents as sample of this research by using simple random sampling method. The data collection method conducted by questionnaire. Based on the descriptive analyses, this paper found that owners-managers of SMEs generally possessed positive or favorable attitude towards sustainability, concerned about social pressures on sustainability, perceived that sustainable entrepreneurship was attractive and perceived themselves as having sufficient ability for sustainable entrepreneurship..